Vision based two-dimensional measurement of machine tool motion trajectory - Haochen HUANG; Daisuke KONO; Masahiro TOYOURA (Journal of Advanced Mechanical Design, Systems, and Manufacturing)
The aim of this study is to develop a vision-based 3D-dynamic motion errors measurement method. In this report, a measurement method is proposed, and its resolution and measurement error in plane motion measurement are discussed. Moreover, the influence of the defocus condition on the detection resolution is analyzed. The displacement of the marker installed on the spindle of the machine tool is obtained through the video captured by the high-speed camera. In order to obtain the displacement of the marker, the center position of the marker is identified by fitting a mathematical function to obtain the position of the intensity peak of the marker. The measurement resolution and accuracy of the proposed method are investigated experimentally. In addition to the model fitting method, the edge detection and threshold detection methods with different functions for model fitting method are also used for marker position detection for comparison. The deviation of model fitting in the results is less than 42 μm compared with the grid encoder as the reference. The standard deviation of the measured static position is less than 0.1 pixel with a defocus length less than 80 mm.